César Vallejo solidario: metonimia, transubstanciación secular y utopía socialista - Brakspear, Owen Fortunato (2022)
This article explores two grammatical characteristics, metonymy and metaphor, in relation to two central themes: the melancholy of death and solidarity between men, as they appear and work together in César Vallejo’s poetry. I propose that in Vallejo’s poetics there is a cooperation between metaphor and metonymy, in the sense that the metonymic connection between linguistic elements works in the poetry as a system that metaphorises the world as a totality of connections in flux. This article suggests that these systems of interconnection and interdependence —both linguistic and physical— are very similar to the scientificophilosophical (that is, Epicurean) system of Lucretius’s De Rerum Natura. This comparison, I conclude, is important for a renewed comprehension of the political and secular worldview of solidarity as it appears in Vallejo’s work.